On the application of some concepts of ring theory to the study of the influence of systems of subgroups of a group - Piskun, M. M.; Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study the groups, in which the family Lnon-nn(G) of all not nearly normal subgroups has the Krull dimension. A subgroup H of the group G is said to be nearly normal if H has finite index in its normal closure.